Utilization of Learning Media in Increasing PAI Motivation and Learning Outcomes at Attin Middle School, Kupang City - Syarif Mamang; Mutohharun Jinan; Syamsul Hidayat; Hafidzd (al-Afkar, Journal For Islamic Studies, 2024)
This study discusses instructional media’s use in increasing motivation and learning outcomes of Islamic Religious Education in Schools and Madrasas. Learning media is an important thing used by teachers to attract interest and foster student motivation in learning, mainly Islamic religious subjects. Students quickly understand the material presented without feeling bored and tired of listening to the teacher’s submission. With the aim, PAI learning materials can be understood and practiced by students after studying at school and madrasa. The method used in this research is quantitative. The findings state that Rasulullāh is an excellent educator who has also used various forms of media in conveying Islamic education to friends so that friends can understand the teachings of Islam properly and correctly. The study results show that learning media can provide an increase in student motivation, greatly assisting teachers in implementing the teaching and learning process to achieve the objectives of learning material. The use of instructional media can also provide a significant influence in improving student learning outcomes in PAI learning in schools and madrasah.